The role of discussion in the institutionalisation of a code of conduct/ethics with specific reference to the adoption of a code of conduct by the South African Police Service - Bernardo, Eric Terblanche (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 1998.